Economic Analysis of Initial Public Offering Underpricing in Stock Market of Pakistan - Ali, Gulzar; Khan, Ansa Javed; Rafiq, Sara (International Journal of Economics and Financial Issues, 2020)
The Initial Public Offering (IPO) underpricing in the stock market is considered an important factor to attract the investor towards the stock. In this study in addition to IPO the economic analysis of underpricing is investigated to examine economic effects of influencing factor of IPO underpricing in stock market of Pakistan for 98 listed companies taking their data for the period of 2013-2018. The findings of the regression analysis indicates that assets return, equities, earnings per share and profit margin are the important factors of IPO underpricing as there economic return to investor has significant, however, the effect of earning-price remains insignificant on IPO underpricing. The descriptive analysis of the study shows maturity of the selected variable and variance influencing factor indicates that the variables isn't multi-collinear with each other. The study concludes that impact of the liquidity level of IPO underpricing in the optional market would help the financial investors in strategizing their speculation through exchanging component. Keywords: Economic Analysis, Initial Public Offering Underpricing, Pakistan Stock Market JEL Classifications: G12, G23, G32 DOI: https://doi.org/10.32479/ijefi.10040